2012
DOI: 10.1158/1055-9965.epi-11-1175
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of DNA Adduct Formation in the Oral Cavity after Drinking Alcohol

Abstract: Background Alcohol consumption is one of the top-10 risks for the worldwide burden of disease and an established cause of head and neck cancer as well as cancer at other sites. Acetaldehyde, the major metabolite of ethanol, reacts with DNA to produce adducts, which are critical in the carcinogenic process and can serve as biomarkers of exposure and possibly of disease risk. Acetaldehyde associated with alcohol consumption is considered “carcinogenic to humans”. We have previously developed the technology to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 26 publications
1
58
0
3
Order By: Relevance
“…As the most abundant DNA adduct, N 2 -ethylidene-2′-deoxyguanosine (N 2 -EtidG), impairs the DNA repair system and apoptosis [26]. The level of N 2 -EtidG is increased in oro-esophageal epithelial cells after alcohol drinking in mice [76] and humans [77]. Moreover, the N 2 -EtidG level is dependent on ALDH2 and ADH genotypes.…”
Section: Disturbance Of Redox Metabolism In Squamous Epithelial Cellsmentioning
confidence: 99%
“…As the most abundant DNA adduct, N 2 -ethylidene-2′-deoxyguanosine (N 2 -EtidG), impairs the DNA repair system and apoptosis [26]. The level of N 2 -EtidG is increased in oro-esophageal epithelial cells after alcohol drinking in mice [76] and humans [77]. Moreover, the N 2 -EtidG level is dependent on ALDH2 and ADH genotypes.…”
Section: Disturbance Of Redox Metabolism In Squamous Epithelial Cellsmentioning
confidence: 99%
“…Further, an elevated risk of hepatocarcinoma and its recurrence occurs among hepatitis C-infected patients with the ALDH2*2 mutation (17). Acetaldehyde levels are particularly high in the saliva after ethanol ingestion (18), leading to a significant increase in acetaldehyde-DNA adduct levels in ALDH2*1/*2 heterozygotes, even after moderate ethanol consumption (19). Because acetaldehyde is a carcinogen, and the duration and extent of exposure influences its toxicity, increasing the rate of acetaldehyde elimination, especially in ALDH2*1/*2 heterozygotes, may reduce important health risks.…”
mentioning
confidence: 99%
“…There are ample evidences showing that exposure to acetaldehyde produce mucosal lesions and adenocarcinomas in the nasal mucosa in rats [ 32 , 70 ]. A study by Balbo and colleague have reported that N 2 -ethyl-2′-deoxyguanosine, a major acetaldehyde derived-DNA adduct was increased by several-fold from baseline after alcohol use in humans [ 2 ]. Genetic evidence suggests that individuals having fast metabolites alleles variants for ADHs [ADH1B*2, ADH1C*1] and the null allele for ALDH 2 [ALDH2*2] have increased acetaldehyde levels and inefficient alcohol metabolism, thereby increasing susceptibility to cancer after alcohol consumption [ 9 , 57 , 7 ].…”
Section: Alcohol Metabolism and Metabolic Enzymesmentioning
confidence: 99%